2019
DOI: 10.1016/j.jot.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Translation of bone wax and its substitutes: History, clinical status and future directions

Abstract: Bone wax, primarily composed of beeswax and softening agent, is a century-old material used to control bleeding of disrupted bone surfaces by acting as a mechanical barrier to seal the wound. The current bone wax products are commonly packed in easy-to-open foil in the form of sterile sticks or plates, with excellent malleability and smooth consistency, enabling cost-effective and easy handling approach for bleeding control. It has also been reported that the inert nature of bone wax causes complications inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 80 publications
0
44
0
1
Order By: Relevance
“…Although rare, such complication has been previously reported, and its application in subtotal petrosectomy should therefore be carefully reconsidered. 13,14 In contrast to bone wax, on histopathological examination Surgicel provokes fewer foreign body giant cells and elicits no inflammation. 15 It is not the material alone, but rather the occlusion technique which seems to play the decisive role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rare, such complication has been previously reported, and its application in subtotal petrosectomy should therefore be carefully reconsidered. 13,14 In contrast to bone wax, on histopathological examination Surgicel provokes fewer foreign body giant cells and elicits no inflammation. 15 It is not the material alone, but rather the occlusion technique which seems to play the decisive role.…”
Section: Discussionmentioning
confidence: 99%
“…In none of our cases was there a clinically relevant foreign body reaction of the used bone wax. Although rare, such complication has been previously reported, and its application in subtotal petrosectomy should therefore be carefully reconsidered 13,14 . In contrast to bone wax, on histopathological examination Surgicel provokes fewer foreign body giant cells and elicits no inflammation 15 …”
Section: Discussionmentioning
confidence: 99%
“…Although bone wax has several benefits, the usage has always raised a concern and is reported to exert clinical problems, including foreign body reaction, poor bone regeneration, infection, and thrombosis 54 . Bone wax is not absorbed by bone spongiosa and it remains at the site impairing bone healing and also aids in bacterial implantation at the site 16,55 …”
Section: Progress In Enhancing Sternal Healing Controlling Bleedingmentioning
confidence: 99%
“…Studies have reported that bone wax significantly reduced the number of bacteria required to initiate infection. It can also inhibit the migration of osteoblasts to the wound site, thereby impairing osteogenesis 55,56 . Its usage was considered as a risk factor for sternal dehiscence and infections, and has come under Class III category (potentially harmful) as per the recent consensus guidelines on sternal wound infection 16 …”
Section: Progress In Enhancing Sternal Healing Controlling Bleedingmentioning
confidence: 99%
“…Günümüzde üretilen testis protezlerinin ameliyathanelerde kolaylıkla stoklanamaması ve tedavi maliyetinin hala yüksek olması gibi dezavantajları vardır. [7] Özellikle beyin cerrahi ve ortopedi alanında yıllarca kullanılmasına rağmen, ciddi bir reaksiyona yol açmayan bone-wax parafin, [8] düşük maliyeti, hemen her ameliyathanede kolayca ulaşılabilmesi ve tunika albuginea içinde çok iyi uyum sağlaması gibi nedenlerle bu çalışmada testis protezi olarak kullanılmıştır.…”
Section: Gereç Ve Yöntemunclassified